The Influence of Parental Support and Training on Athlete Performance with Motivation as Mediation Variable - Irma Rahayu; Agustinus Setyawan (Research Synergy Foundation, 2025)
Internal and external factors generally influence athlete achievement. The internal factor that mainly influences the athlete's achievement is motivation. Meanwhile, the external factors are parental support and training attained. The research intended to examine the influence of parental support and training on young athletes' performance in Tanjungpinang. A survey research design was carried out using a questionnaire for data collection. Using purposive sampling, the sample calculation results, with an acceptable margin of error of 0.05, showed 194 confirmed samples from various individual and team sports, ages ranging from 8 to 23. The instrument used for data analysis was SmartPLS (Partial Least Squares) software to confirm theories and forecast relationships between variables. The questionnaire was distributed using Google Forms and shared via WhatsApp. This result indicated that parental support directly and mediated by motivation is ineffective in improving athlete performance, while training has a positive and significant influence both directly and through motivation. This research is limited in scope and is only conducted in Tanjungpinang, with a narrow scope of the research and limitations in the variables studied. The study results provide insight for athletes and coaches. The inclusion of parental involvement in the context of sports performance and suitable training concepts will significantly improve athlete performance. This study simultaneously discusses parental support and training and the mediation of motivation to improve athlete performance.